Lifeworld dimensions in language education and the integration of refugee students in Germany: Results from a study with Ukrainian refugees - Orobchuk, Dariia; Skintey, Lesya (Glottodidactica, 2024)
This paper examines the educational challenges and language acquisition processes of newly immigrated students in Germany, with a focus on children and adolescents who have fled Ukraine. Utilizing qualitative interviews with Ukrainian refugees, the study explores the impact of migration, particularly due to the Russian war against Ukraine, on the language education of these individuals in German as a Second Language settings. The interviews, which were conducted with women who have fled Ukraine, and include their perspectives on familial language practices and educational orientations, reveal the complexities faced by this population in their host country. The paper discusses the implications of experiences of flight, language use within the family, structural changes in educational approaches, and the Ukrainian online schooling in sustaining educational continuity. The findings underscore the need for trauma sensitive, culture informed, and language specific pedagogy, alongside the importance of considering the emotional and psychological wellbeing of refugee students. The paper calls for more nuanced research, and didactic considerations that align with the diverse linguistic and educational backgrounds of refugee students.